Photothermal lens technique: a comparison between conventional and self-mixing schemes. (4th April 2019) - Cabrera, H; Ashraf, I; Matroodi, F; Ramírez-Miquet, E E; Akbar, J; Suárez-Vargas, J J; Barrera Ramírez, J F; Korte, D; Budasheva, H; Niemela, J
Abstract: This work focuses on assessing the analytical capabilities of a new photothermal lens method based on the self-mixing effect to reliably measure metallic traces in water-ethanol solutions. We compare it with the conventional thermal lens scheme, considering the low detection limit and versatility. A theoretical model is presented to describe the laser power variations as a function of the photothermal parameters of the analyzed sample. The experimental results demonstrate that the laser intensity variations, induced by the external optical feedback, are governed by the photothermal lens effect. Measurements of Fe(II)-1, 10-phenanthroline in water–ethanol solutions show a favourable correspondence and agreement with the theory. The low detection limits obtained by the two analytic techniques also agree very well. Nevertheless, our instrument presents advantages regarding compactness and simplicity, suggesting that this platform could be potentially useful as a robust analytical tool for metallic trace detection. In addition, calibration of the method is performed by measuring the so-called self-mixing constant.